Laparoscopy‐assisted distal gastrectomy for multiple adenocarcinomas in intrathoracic upside‐down stomach. Issue 1 (18th January 2016) - Namikawa, Tsutomu; Fukudome, Ian; Munekage, Eri; Munekage, Masaya; Maeda, Hiromichi; Kitagawa, Hiroyuki; Mibu, Kiyo; Nagata, Yusuke; Kobayashi, Michiya; Hanazaki, Kazuhiro
Abstract: Herein we report on a case of two adenocarcinomas arising from an upside‐down stomach in an elderly patient. An 83‐year‐old man was referred to our hospital with gastric cancer. Esophagogastroduodenoscopy showed two superficial depressed lesions in the stomach that were confirmed on biopsy as constituting a moderately differentiated tubular adenocarcinoma. CT and an upper gastrointestinal barium study revealed that the entire stomach and parts of the duodenum were located in the mediastinum. The patient underwent laparoscopy‐assisted distal gastrectomy and regional lymph node dissection with Billroth I reconstruction, followed by reduction of the migrated stomach. The hiatal defect was closed by primary suturing of the right and left crura at the anterior space of the esophagus. The patient's postoperative course was good, and follow‐up after discharge was uneventful. To the best of our knowledge, this is the first case report of multiple adenocarcinomas in an upside‐down stomach treated by laparoscopy‐assisted distal gastrectomy.